Asian and African lineage Zika viruses show differential replication and innate immune responses in human dendritic cells and macrophages - Pamela Österlund; Miao Jiang; Veera Westenius; Suvi Kuivanen; Riia Järvi; Laura Kakkola; Rickard Lundberg; Krister Melén; Miša Korva; Tatjana Avšič – Županc; Olli Vapalahti; Ilkka Julkunen (NATURE PUBLISHING GROUP, 2022)
Zika virus (ZIKV) infections in humans are considered to be mild or subclinical. However, during the recent epidemics in the Pacific Islands and the Americas, the infection was associated with Quillain-Barre syndrome and congenital infections with fetal brain abnormalities, including microcephaly. Thus, more detailed understanding of ZIKV-host cell interactions and regulation of innate immune responses by strains of differential evolutionary origin is required. Here, we characterized the infection and immune responses triggered by two epidemic Asian/American lineage viruses, including an isolate from fetal brains, and a historical, low passage 1947 African lineage virus in human monocyte-derived dendritic cells (DCs) and macrophages. The epidemic Asian/American ZIKV replicated well and induced relatively good antiviral responses in human DCs whereas the African strain replicated less efficiently and induced weaker immune responses. In macrophages both the African and Asian strains showed limited replication and relatively weak cytokine gene expression. Interestingly, in macrophages we observed host protein degradation, especially IRF3 and STAT2, at early phases of infection with both lineage viruses, suggesting an early proteasomal activation in phagocytic cells. Our data indicates that ZIKV evolution has led to significant phenotypic differences in the replication characteristics leading to differential regulation of host innate immune responses.